Propuesta para la creación de una unidad estratégica para la comercialización de aires acondicionados con funcionamiento a gas natural en la empresa Gases de Occidente (2023)
Technological innovation in the use of gas appliances has led the industry to develop solutions tailored to needs, including air conditioning equipment that runs on natural gas, impacting people's comfort and quality of life by being able to counteract strong climates, on the other hand, in the commercial and industrial field by facilitating the conditions for production processes.